Emicizumab prophylaxis among infants and toddlers with severe hemophilia A and inhibitors—a single‐center cohort. Issue 11 (26th July 2019) - Barg, Assaf A.; Avishai, Einat; Budnik, Ivan; Levy‐Mendelovich, Sarina; Barazani, Tami B.; Kenet, Gili; Livnat, Tami
Abstract: Background: Emicizumab is a bispecific antibody that bridges factor IXa and factor X to restore hemostasis in patients with hemophilia A (HA). Its efficacy and safety have been proven in multicenter trials. However, real world data regarding its use in very young children are currently lacking. Ancillary test results for monitoring emicizumab's hemostatic effect and their clinical correlations are scarce. Methods: Children with HA and inhibitors treated by emicizumab were prospectively followed at our center. Laboratory follow‐up included rotational thromboelastometry (ROTEM) and thrombin generation (TG), prior to and during treatment. Results: Eleven children whose median age was 26 months were treated by emicizumab and followed for a median of 36 weeks. During follow‐up, none experienced hemarthrosis or any other spontaneous bleeds. For 7/11 patients, emicizumab prophylaxis was sufficient to maintain hemostasis without additional supplemental therapy. Only 4/11 patients were occasionally treated with recombinant activated FVII for trauma. Two minor surgeries were safely performed without supplemental therapy while another procedure was complicated by major bleeding. TG parameters improved for all patients, correlating with their clinical status. Interestingly, the lowest TG values were obtained for patients experiencing bleeding episodes, while ROTEM parameters in all patients were close to the normal range. Conclusions: This study confirms the safety and efficacy of emicizumab in reducing bleeds in young children with HA with inhibitors, including infants. However, surgeries warrant caution as emicizumab prophylaxis may not be sufficient for some procedures. TG may more accurately reflect the hemostasis state than ROTEM in pediatric patients treated with emicizumab.